ممارسة القيادة التحويلية لدى مديري المدارس وأثرها في التنمية المهنية للمعلمين في محافظة مسندم بسلطنة عمان - شحية، نبيلة عبد الله علي (Kulliyah of Education, International Islamic University Malaysia, 2021)
The study aimed to exmine the influence of transformational leadership practiced by primary school principals in teachers' professional development from teachers' perspctives. The population included all teachers (256) teaching grades (5-12) in the Musandam Governorate in the Sultanate of Oman. A stratified random sample consisting of (154) teachers (100 male and 54 female) was selected from the population. The correlational descriptive approach, using a questionnaire, was utilized to answer the research questions. The descriptive and inferential statistics and multiple regression were used in data analyses. The analyses showed that teachres perceived transformational leadership practices to be very high among school principals, with no statistically significant differences in teachers'perciption by gender and years of expereince (p>0.05). The analyses also showed that teachers perceived the professional development given to teachers by the the schools' principals was very high, with no statistically significant differences in teachers'perciption by gender and years of expereince (p>0.05). Moreover, there was a statistically significance effect for the independent variable (transformational leadership) on the dependent variable (teachers' professional development). Pursuant to the findings, the this research uurges to continue including transformational leadership in the school leadership programs being implemented by the Specialized Institute for the Professional Training of Teachers, to target the new school principals, new school principals' assistants and in-srevice principals. Furthermore, school principals should give more attention to the implementation of professional development programs that include the three components of professional development (knowledge, skills, attitudes and values). To obtain a greater depth of understanding regarding transformational leadership among school principals, qualitative research is, therefore, recommended.